A Success Story: Improving Documentation of Medical Device Patient Safety Events - Casagrande Cesconetto, Alice (CMBES Proceedings, 2023)
Improving documentation of medical device patient safety events in the computerized maintenance management system used by Lower Mainland Biomedical Engineering.